2011
DOI: 10.1002/ejlt.201100004
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids of Thespesia populnea: Mass spectrometry of picolinyl esters of cyclopropene fatty acids

Abstract: Thespesia populnea belongs to the plant family of Malvaceae which contain cyclopropane and cyclopropene fatty acids. However, previous literature reports vary regarding the content of these compounds in Thespesia populnea seed oil. In this work, the content of malvalic acid (8,9-methylene-9-heptadecenoic acid) in the fatty acid profile of Thespesia populnea seed oil was approximately 7% by GC. Two cyclopropane fatty acids were identified, including dihydrosterculic acid. The methyl and picolinyl esters of Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…A few reports have appeared that discuss the composition of T. populnea seed oil. Subbaram [6] reported an iodine value for T. populnea seed oil that seems low (71.5) given his and other reported fatty acid profiles for the oil [6][7][8]. The value obtained in this work (98.8) is in better agreement with the reported fatty acid data.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A few reports have appeared that discuss the composition of T. populnea seed oil. Subbaram [6] reported an iodine value for T. populnea seed oil that seems low (71.5) given his and other reported fatty acid profiles for the oil [6][7][8]. The value obtained in this work (98.8) is in better agreement with the reported fatty acid data.…”
Section: Discussionsupporting
confidence: 86%
“…Among these were seeds of Thespesia populnea. Chromatography of the methyl esters from this plant's seed oil suggested that the oil contained 10-to 20-fold higher levels of these oddchain fatty acids, which have not been mentioned in prior analyses of the plant's oil [6][7][8].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Sterculic acid was identified by the shift of the characteristic peaks to m/z 286 and 293 but was present only in very minor amounts. The mass spectral cleavage pattern, which corresponds to that of picolinyl malvalate [33], albeit with a shift of 14 amu for peaks generated by cleavage between the picolinyl and cyclopropenyl moieties, agrees with other results [34]. On the other hand, dihydrosterculic acid was present in amounts similar to malvalic acid while dihydromalvalic acid was not observed, which could be due to peak overlapping or minute amounts thereof.…”
Section: Resultssupporting
confidence: 90%
“…Besides this observation, several cyclic fatty acids not previously discussed or quantified in kenaf seed oil were detected. The presence of malvalic acid was unambiguously shown by the mass spectrum of its picolinyl ester which displays a typical pair or peaks at m/z 272 and 279 in the corresponding mass spectral pattern discussed previously [33]. The presence of malvalic acid, which has an unusual odd-numbered (C17) fatty acid chain can be seen in conjunction with the presence of 8-heptadecenoic acid, as heptadecenoic acid is likely the biogenic precursor of malvalic acid [21].…”
Section: Resultsmentioning
confidence: 64%